The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.02.25.964551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causes of death in newborn C57BL/6J mice

Abstract: 22Neonatal mortality in wild-type laboratory mice is an overlooked welfare and financial 23 problem in animal facilities around the world. Causes of death are often not reported 24 and its causes remain unknown. 25 In this study, 324 newborn pups from two breeding colonies of healthy wildtype 26 C57BL/6 mice underwent post-mortem analysis with special focus on obtaining proof 27 of life after birth, evaluation of stomach contents and observation of congenital 28 abnormalities that could compromise sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Most often, when there are two females sharing a cage, they also share the same nest, and younger lighter pups get clustered together with the older, heavier, and more mobile pups. Data on post-mortem inspection performed in 324 C57BL/6J pups found dead, by the authors of this study, revealed that 24% of the pups had some kind of traumatic lesion, including bite wounds and bruises [25].…”
Section: Pup Probability Of Deathmentioning
confidence: 61%
“…Most often, when there are two females sharing a cage, they also share the same nest, and younger lighter pups get clustered together with the older, heavier, and more mobile pups. Data on post-mortem inspection performed in 324 C57BL/6J pups found dead, by the authors of this study, revealed that 24% of the pups had some kind of traumatic lesion, including bite wounds and bruises [25].…”
Section: Pup Probability Of Deathmentioning
confidence: 61%
“…Parental animals must balance caregiving behaviors with other behaviors required for their own survival, making single parenting especially challenging. Previous studies of rodents and other species report a remarkably high degree of infant mortality, both outdoors in native habitats and animals housed in laboratory conditions-although it remains controversial how much infant mortality occurs for isolate vs communally-rearing mothers (König, 1993; Manning et al, 1995; Ferrari et al, 2019; Capas-Peneda et al, 2020; Brajon et al, 2021). We aimed to resolve when and how pup mortality occurs, if it is due to parental neglect or other factors, and if mouse mothers might learn from certain experiences to improve maternal care over subsequent litters.…”
Section: Main Textmentioning
confidence: 99%
“…Consequently, there is decreased breeding performance, which has been associated with a reduced welfare in laboratory rodents. [1][2][3][4] Although the mortality rate reported in laboratory mice is high, there is limited knowledge on how pups die. Investigating the different reasons which lead to pups' death is the key to preventing a lower performance in mouse reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is decreased breeding performance, which has been associated with a reduced welfare in laboratory rodents. 1 4…”
Section: Introductionmentioning
confidence: 99%